Exploring Social Psychology - Myers David G (Mcgraw Hill, Inc, 1994)
The ultimate brief text in social psychology - a quick overview of the field packaged to suit students' attention spans. Foreword, Preface, Doing Social Psychology, Did You Know It All Along?, Social Thinking, Intuition: The Power and Limits of Our Inner Knowing, Reasons for Unreason, Clinical Intuition: The Perils of Psychologizing, The Fundamental Attribution Error, A New Look at Pride, The Power of Positive Thinking, Behavior and Belief, Who is Miserable - and Why?, Who is Happy - and Why?, Social Influence, East Meets West: Individualism and Collectivism and Communitarianism, Gender and Genes, How Nice People Get Corrupted, Two Routes to Persuasion, Indoctrination and Inoculation, The Mere Presence of Others, Many Hands Make Diminished Responsibility, Doing Together What We Would Never Do Alone, Power to the Person, Social Relations, The Dislike of Diversity, The Roots of Prejudice, The Nature and Nurture of Aggression, Causes of Conflict, Blessed are the Peacemakers, Who Likes Whom?, Epilogue: Big Ideas in Social Psychology and Religion, References, Acknowledgements, Name and Subject Index.